The Image of Dido in 15th-Century Italian Painting: An Area of Interpretation - Piven, Marina G. (Actual Problems of Theory and History of Art, 2019)
The growing attention to humanistic culture in 15th-century Italy led to the emergence of figures that came from ancient poetry and history. In the paintings on ancient plots artists visualized ideals of morality, the nobility of deeds, and relationship between the fate of human, and the chosen life path. In the circle of most popular female characters in Quattrocento secular painting was the image of Dido, legendary Carthaginian Queen. Her story was known in Renaissance Italy in several versions: from the writings of ancient historians, Roman poetry, medieval knightly novels. The essay attempts to show diversity of semantic contexts that determined Dido’s tragic image interpretations in Quattrocento Italian painting.The features of artistic embodiment of legendary and poetic plots are considered on domestic narrative paintings (wedding chests of the workshops Apollonio di Giovanni, and Francesco di Giorgio Martini), and compositions of Liberale da Verona and Andrea Mantegna. The article focuses on important principles in visual representation of images: the structure of pictorial narrative, expressive means, characteristic attributes.